Turbidimetric Determination of Metoclopramide Hydrochloride in Pharmaceutical Preparation via the Use of A new Homemade Ayah 6SX1-T-2D Solar Cell-Continuous Flow Injection Analyser - S. Turkie Al-Awadie, Nagam; H. Ismael Al-saadi, Kefah (Iraqi Journal of Science, 2023)
A newly developed analytical method characterized by its speed and sensitivity for the determination of metoclopramide hydrochloride (MCP-HCl) in pure and pharmaceutical preparation via turbidimetric measurement (0-180o) by Ayah 6SX1-T-2D Solar cell-CFI Analyser. The method was based on the reaction of phosphomolybdic acid with metoclopramide hydrochloride in acidic medium to form yellowish white precipitate for the ion-pair complex. Turbidity was measured via the reflection of incident light that collides on the surface precipitated particles at 0-180o. Chemical and physical parameters were studied and optimized. The calibration graph was linear in the range of 0.0005-3 or 0.0005- 4 mMol.L-1, with correlation coefficient r = 0.9947&0.9845 respectively. The limit of detection 3.543 ng/sample from the step wise dilution for the minimum concentration in the linear dynamic ranged of the calibration graph with RSD% lower than 0.3% for 1, 3 mMol.L-1 (n=8) concentration of metoclopramide hydrochloride . The method was successfully applied to the determination of metoclopramide hydrochloride in three pharmaceutical drugs. A comparison was made between the newly developed method analysis with the classical method (HANNA instrument for turbidity measurement) using the standard addition method via the use of t-test. It was noticed that there was no significant difference between two methods at 95 % confidence level.